Sex-specific seasonal body mass variation in the Pale-breasted Thrush (Turdus leucomelas) - Floreste, Felipe Rangel [UNESP]; Batisteli, Augusto Florisvaldo; Pizo, Marco Aurélio [UNESP] (Springer Nature, 2021)
Body mass variation is an effective way to evaluate the effect of seasonality on the physiological status of individuals. The breeding period is critical for altricial birds in terms of energy balance and leads to sex-specific demands in species with asymmetrical division of parental care. However, seasonal body mass variation is still poorly known in Neotropical birds, which share a suit of life-history traits, and sex-related seasonal body mass variation in birds is poorly studied overall. Here, we investigate body mass variation between the sexes in both breeding and non-breeding periods in two suburban populations of a Neotropical bird with asymmetric division of parental tasks, the Pale-breasted thrush (Turdus leucomelas). Using wing length as a covariate in a linear mixed-effects model, we found that thrushes were heavier in the breeding period, and that sexual difference in body mass was only marginally significant (males: 67.62 ± 3.75 g, females: 71.30 ± 4.24 g, n = 218 captures of 152 individuals). However, the interaction between sex and period was significant, and a post hoc test revealed that males were lighter than females only during the breeding period. We suggest that the sex-specific seasonal variation in body mass results from distinct parental care activities performed by each sex during the breeding period.
Keywords: Body condition; Neotropical birds; Parental care; Seasonality; Sexual conflict